Geographical information system mapping and carbon stock assessment of the experimental forest area - Diamante, Cecille C. (2014)
This study assessed the carbon stock of the land use within the Experimental Forest Area (EFA) of the Western Mindanao State University (WMSU) and analyzed its geo-spatial distribution using the Geographical Information System (GIS) model. Field measurements and laboratory analysis were used to measure the biomass density and carbon stock of the samples. The statistical tools used were one-way ANOVA and normality test. The geo-spatial distribution of carbon stock generated in GIS produced a GIS map of the land use of the study area. Based from the result of the study, site 5 (Closed forest canopy) attained the highest biomass density (615.63), carbon stock (176.41-249.74MgC/ha) and CO₂ equivalent (190.58-283.42 CO₂ e/ha) among the six sites. The lowest biomass density of 58.35 Mg/ha was shown in Site 2 (Brushland) while the lowest amount of carbon stock (101.25 MgC/ha) was observed in Site 1 (Breeding Farm) and lowest CO₂ equivalent of 2.41 Mg CO₂ e/ha was found in Site 2 (Brushland). Among the various carbon pools, the tree obtained the highest mean biomass (192.81 Mg/ha) and carbon stock (86.98 MgC/ha) while the understory vegetation got the lowest mean biomass (3.55 Mg/ha) and lowest carbon stock was observed in the litter (5.65 MgC/ha). Mapping the data in GIS and sharing it with the other stakeholders can encourage more active community participation to advocate protection and conservation of the existing land use as it is part of watershed boundaries.
Keywords: Forests and forestry; Mindanao studies